Development of augmented reality application as a learning tool in biology education - Yong, Mei Ting (2024)
This project presents the development of an Augmented Reality (AR)-based mobile application designed as a learning supplement specifically for secondary biology students in Malaysia. Although many countries have widely adopted AR technology in the education field, AR technology in education in Malaysia remains in its start-up and trial stage. There is a lack of dedicated applications that fit the school syllabus in Malaysia, and most schools still teach biology using traditional methods such as textbooks. While some biology-related AR applications exist on the market, their scope is typically general and may not serve as effective learning tools for students. To address these issues, this project aims to develop a Markerless AR mobile app that enables students to learn abstract concepts in a more engaging way by interacting with biological models virtually in the real world, without the need for markers. Additionally, to maximize the app’s effectiveness, a gamified quiz module is integrated to reinforce learning through interactive assessments, promoting student engagement and retention. The app has undergone comprehensive system testing, expert evaluations, and user experiments to assess its effectiveness in improving educational outcomes. This project contributes to the modernization of biology education in Malaysia, offering a more immersive, interactive, and enjoyable learning experience for students.